Morphological and anatomical aspects of the leaves of Rhizophora mangle L. (Rhizophoraceae) under different lighting conditions - Augusto da Silva, Camilla Reis; dos Santos Silva, Marcelo; dos Santos Lopes Ferreira, Léa Maria; Batista Leite, Kelly Regina; Benedito da Silva, Lazaro (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2016)
The basis of differentiation between sun and shade leaves is related to different light intensities. In order to understand the adaptability of the leaves of Rhizophora mangle L., associated with different lighting conditions, leaves were collected from the upper peripheral six individuals (sun leaves) and the lower region of the same internal (shade leaves). The variables analyzed leaf thickness, palisade parenchyma, adaxial and abaxial epidermis, adaxial and abaxial cuticle, stomatal density and index. Measurements were made ??on microscope equipped with ocular micrometer. Sun leaves were lower and with more xeromorphic characteristics, such as increased thickness of the cuticle and the adaxial and abaxial epidermis. The palisade parenchyma and limbus showed up thicker than shade leaves, with no significant difference between the cuticle of the abaxial surface. It was also observed a higher frequency of stomata per mm², an average of 70/mm², while shade leaves showed 47/mm², with no differences between length and width. Differences between the sun leaves and shade leaves indicate adaptive capacity of this species to remain active at different light conditions.